Research in Spain and Latin America on Journalism Through Doctoral Theses - Lozano-Ascencio, Carlos (2022)
Ph.D. theses represent the culmination of post-graduate education for doctoral candidates, and are also the starting point for junior researchers’ academic careers. Post-graduate studies in Journalism allow in-depth research into different aspects of reality. In that sense, a Ph.D. thesis represents an intense, in-depth piece of work which observes social facts linked to different knowledge perspectives. Studying the acquisition of a Ph.D. through a piece of research is a way to gain more in-depth knowledge of post-graduates in Journalism coming from Spanish universities. The study has the Communication (Journalism, Audiovisual Communication, Advertising, and Public Relations) theses defended in Spanish universities as its raw material: some 2784 pieces of work registered between 2007 and 2018. The research unit of analysis focuses exclusively on theses on Journalism defended between 2014 and 2018 (a total of 506 Ph.D. theses, 67 of them with direct references to Latin America). Data analysis reveals that Journalism is one of the central themes in the field of Communication; documents (either printed, audiovisual or digital) are the main units of analysis. The predominant research techniques center on content and discourse analysis. In terms of methodology, the open-access archive of MapCom (https://mapcom.es/) was used to analyze the subjects under study, the epistemological approaches, and the research methods.